Strengthening Financial Infrastructure - Deposit Insurance and Lending of Last Resort - Richard Dale; Franco Bruni; Christian de Boissieu (SUERF - The European Money and Finance Forum, 2000)
1) Deposit Insurance in Theory and Practice by Richard Dale. 2) Lending of Last Resort and Systemic Stability in the Eurozone by Christian de Boissieu and Franco Bruni. The first paper overviews theoretical arguments for and against deposit insurance, a system that can be aimed at consumer protection and/or at financial stability. But deposit protection, by reducing risk, can cause " moral hazard" , in particular in relations to institutions potentially "too-big-to-fail" . The US and Japanese experiences with deposit insurance are useful lessons for Europe as they demonstrate how badly can market participants be affected by moral hazard. The second paper discusses lending of last resort in the Eurozone. The authors support the ECB's view that this function must be confined to play a minor role and that it must be handled with 'constructive ambiguity'. However, they think explicit decisions and a clear division of responsi-bilities are needed to ensure that its role is really minor and that the ambiguity is in fact constructive. They call for euro-wide standards of supervision and for the establishment of a 'European Observatory of Systemic Risk'. They also recommend " prompt corrective action" with the authorities ready to close banks before they become insolvent, if they do not comply with their instructions to keep high capital ratios. Read together the two papers offer useful insights into the current debate about how to make the financial infrastructure of Europe more robust.
Keywords: 330; Financial infrastructure